Design a D-shaped single mode fiber SPR sensor with a composite nanostructure of HMM/monolayer graphene for DNA hybridization detection. (February 2023) - Gao, Jinjuan; Jiang, Shouzhen; Yang, Wen; Liu, Runcheng; Feng, Jingwen; Zha, Zhipeng; Zhang, Chao; Jiang, Mingshun; Fan, Xiuwei
Graphical abstract: Highlights: A monolayer graphene/HMM/D-SMF SPR sensor was designed, which could detect DNA molecules and analyze the kinetic hybridization properties of the DNA molecules. The internal Bloch wave vector of the HMM was calculated, the mode phase matching was analyzed, and graphene gain was achieved. Experimental results show that the sensor exhibited high sensitivity, good linearity, and repeatability. The sensor could detect the region from visible light to near infrared, so it could serve as a novel detection method for other biomolecules. Abstract: The detection of DNA sequence hybridization has taken on a critical importance for the research of life science, microbiology, and environmental science. In this paper, a D-shaped single mode fiber (SMF) SPR sensor with a composite nanostructure of hyperbolic metamaterials (HMM)/monolayer graphene was developed for DNA detection. The dispersion relation of the Bloch wave in HMM and the energy conversion between modes in plasma resonance were confirmed through calculation and simulation. During the experiment, the metamaterial combined with a monolayer graphene composite structure exhibited the sensitivity and quality factor of 5000 nm/RIU and 40 RIU −1, respectively. The sensor based on the optimal parameters was adopted to detect the hybridization of DNA molecules, and the affinity and reaction rates of DNA molecular hybridization were analyzed based on molecular reaction kinetics. As revealed by the results of this study, the sensor had the advantages of miniaturization, low cost, and specificity detection, which could serve as a novel sensor for DNA hybridization detection from visible light to near infrared region.